Chloroplast Genome Evolution in Four Montane Zingiberaceae Taxa in China - Yang, Qian; Fu, Gao-Fei; Wu, Zhi-Qiang; Li, Li; Zhao, Jian-Li; Li, Qing-Jun (Frontiers in Plant Science, 2022)
Chloroplasts are critical to plant survival and adaptive evolution. The comparison of chloroplast genomes could provide insight into the adaptive evolution of closely related species. To identify potential adaptive evolution in the chloroplast genomes of four montane Zingiberaceae taxa (Cautleya, Roscoea, Rhynchanthus, and Pommereschea) that inhabit distinct habitats in the mountains of Yunna, China, the nucleotide sequences of 13 complete chloroplast genomes, including five newly sequenced species, were characterized and compared. The five newly sequenced chloroplast genomes (162,878–163,831 bp) possessed typical quadripartite structures, which included a large single copy (LSC) region, a small single copy (SSC) region, and a pair of inverted repeats regions (IRa and IRb), and even though the structure was highly conserved among the 13 taxa, one of the rps19 genes was absent in Cautleya, possibly due to expansion of the LSC region. Positive selection of rpoA and ycf2 suggests that these montane species have experienced adaptive evolution to habitats with different sunlight intensities and that adaptation related to the chloroplast genome has played an important role in the evolution of Zingiberaceae taxa.